(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background-Whole body vibration (WBV) exercise is a curative strength and a feasible exercise technique that has received considerable attention in recent years.to date there is no evidence of effect of whole body vibration therapy in hamstring flexibility in osteoarthritis patients. Objectiveof the study was to investigateand compare the effect of whole body vibration therapy on hamstring flexibility and comparing it with passive stretching technique to increase hamstring flexibility in patients with knee osteoarthritis. Methodology: In this Experimental study 30 patients were selected for the study based on inclusion and exclusion criteria. Convenient sampling was used to divide patients into 2 groups. Experimental group- whole body vibration therapy, control group- passive stretching technique. Both the groups were assessed pre-intervention and after intervention for hamstring flexibility. Outcome measures were “sit and reach” test (SRT) and “active knee extension” test (AKE).